Zero temperature quantum properties of small protonated water clusters (H2O)(n)H+ (n=1-5) - Mella, M; Clary, D (2003)
The structure and vibrational motion of the protonated water clusters (H2O)nH+ (n=1-5) were studied using the OSS3 interaction potential and the diffusion Monte Carlo (DMC) method. The aim was to simulate their ground state eigenfunctions. An attempt was also made to compute the ground state energy for neutral water clusters using the same potential to obtain reference values for their proton affinity. The resultant data wer analyzed in detail.